Development of Vertical Shading Parameter Model for Reducing Energy Consumption in Tall Building based on Overall Thermal Transfer Value - A Case Study - Miptahul Hajji, Apif; Ariestadi, Dian; Hidayat, M. Nuril (International Journal of Sustainable Construction Engineering and Technology, 2023)
In tall building, shading design is a configuration that includes geometry, material, and the system. Currently, the design of the shade found for building’s envelope is not only used to improve the thermal performance, but is also required to provide aesthetic value to the appearance of a building. The use of shading design in the form of vertical shade at certain places will provide differences in the acquisition of sunlight for interior spaces. Therefore, by shading design the appearance will certainly affect the thermal performance of the building envelope. This study aims to develop and propose a model that can be used as parameter measures of the effect of shading design variations on the thermal performance of the building envelope. This variation will include shading design concept which applies different vertical shading that covers glass material, the shading width, and the shading angle. This research design includes the calculation of the shade coefficient (SC) and overall thermal transfer value (OTTV) of each variant, followed by using multiple linear regression (MLR) analysis with manufacturer’s SC glass, shading width, and shading angle as the predictor variables. The study is conducted by two parts: designing of vertical shading parameters that affect the value of the SC and determining the thermal performance of the building. The MLR analysis is carried out to obtain a linear equation showing the effect of shading design on thermal performance of the building envelope. Based on the regression analysis result, it can be seen that the manufacturer’s SC of glass has the biggest impact on the OTTV value, while the shading angle has the lowest. With 95.2%-98% of the predictors data can explain the value of OTTV, the model can be used as the tool for designing vertical shading for reducing the energy consumption in the building.